PENGARUH INFLASI, KURS, DAN HARGA MINYAK MENTAH DUNIA TERHADAP INDEKS HARGA SAHAM GABUNGAN - Teguh Prasetyo; Dwi Susilowati; Nadi Hernadi Moorcy (Fakultas Ekonomi Universitas Balikpapan, 2022)
The purpose of this study was to determine the effect of Placement, Job Training and Motivationon the Moraleof the Employees of PT. ASDP Indonesia Ferry (Persero) in Balikpapan.The population in this study were permanent employees as much as 222 respondents.By using random sampling techniques so the sample that is in use as much as 111respondents.Data collection techniques are observation, interviews and questionnaires.The data analysis technique used is Multiple Linear Regression using program SPSS v22. The results showed Placement, Job Training and Motivationsimultaneously affect the Morale of employees PT. ASDP Indonesia Ferry (Persero)in Balikpapan. Motivationpartially hadsignificant influence and dominant to the morale of employees of PT. ASDP Indoensia Ferry (Persero) in Balikpapan.